Paleocorrentes e paleogeografia do Grupo Aerado, cretáceo inferior da Bacia Sanfranciscana - Mescolotti, Patricia Colombo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Areado Group of the Sanfranciscana Basin is a Lower Cretaceous continental sedimentary system that is correlated to the Brazilian Pre-Salt beds. The Aerado Group is composed of Abaeté, Quiricó and Três Barras formations. Paleocurrent data for the Areado Group were previously presented, although not systematically which prevented significative interpretations on the basin paleogeography. This work attempts to systematically evaluate paleocurrent data, aiming to recognize depositional environment and paleogeographic reconstruction, based on the sedimentary facies and paleocurrents measurements along vertical profiles. Fluvial paleocurrents of the Abaeté Formation indicate paleoflows towards NW whereas aeolian palecurrents of the Três Barras Formation show paleowinds towards SW. The depositional systems interpreted for the Areado Group were: braided river, alluvial fan, lacustrine, playa lake, fluvial-deltaic and aeolian. The combined analyses of facies and paleocurrents allowed a reliable paleogeographic reconstruction of the basin, with paleodip towards northwest, paleowinds towards south-southwest and source-area located at southeast. These results indicate that paleowinds were orthogonal to paleostream, but parallel to depositional strike of the basin. The interpreted depositional systems characterize a desert environment during the Abaeté sub-basin times. The association of dunes and wet interdunes followed by large scale dunes and dry interdunes suggests a decrease in humidity towards the top of the Três Barras Formation, with a dry aeolian system onlapping the basement. The observed decrease of humidity in Sanfranciscana Basin may reflect local or regional paleoclimatic changes during the opening of the South Atlantic, but this assumption is only tentative

O Grupo Areado, da Bacia Sanfranciscana, é um sistema sedimentar continental eocretácico e cronocorrelato ao Pré-sal. Ele divide-se nas formações Abaeté, Quiricó e Três Barras. Alguns trabalhos trataram de paleocorrentes para o Grupo Areado, mas sempre com enfoque secundário e com baixas quantidades de medidas. Esse trabalho buscou descrever as fácies sedimentares e analisar de forma sistemática as paleocorrentes desse grupo, visando obter os ambientes deposicionais e a reconstituição paleogeográfica para a bacia. Foram levantadas seções estratigráficas verticais, descritas fácies e levantadas estações de paleocorrentes. Como resultado obtiveram-se paleocorrentes fluviais para NW (Fm. Abaeté) e paleocorrentes eólicas para SW (Fm. Três Barras). Os sistemas deposicionais interpretados para o Grupo Areado foram: rio entrelaçado, leque aluvial, lacustre, playa lake, flúvio-deltaico e eólico. Com a análise das paleocorrentes e das fácies sedimentares reconstituiu-se cenário paleogeográfico mais fidedigno para a bacia, com paleomergulho deposicional para NW, área fonte para SE e peleoventos com sentido para SSW. Assim sendo, os paleoventos eram ortogonais à paleodrenagem, mas paralelos ao strike deposicional da bacia. Os sistemas deposicionais interpretados caracterizam ambiente desértico para a Sub-Bacia Abaeté. A associação de dunas e interdunas úmidas sendo sucedidas por dunas de grande porte e interdunas secas, pouco desenvolvidas, sugere um decréscimo de umidade para o topo da Fm. Três Barras, sendo que o sistema eólico seco extrapolou os limites iniciais da sub-bacia. O decréscimo de umidade observado na Bacia Sanfranciscana pode ser reflexo de mudanças paleoclimáticas locais ou regionais durante a abertura do Atlântico Sul, contudo carece de mais estudos para entender melhor esta mudança
Keywords: Geologia estratigráfica; Paleocorrentes; Paleogeografia; Facies (Geologia); Minas Gerais